Hubungan Hygiene Sanitasi Pedagang Ikan Pindang Dengan Jumlah Bakteri Ikan Pindang Di Pasar Anom Desa Kolor Kabupaten Sumenep - Qoriatul Wahida; Moch Agus Krisno Budiyanto; Fendy Hardian Permana; Elly Purwanti; Fuad Jaya Miharja; Riyanto . (Jurnal Pangan dan Gizi, 2022)
The level of contamination of pindang fish is quite high. The factor of decreasing the quality of pindang fish is due to the lack of sanitation and hygiene from business actors (pindang fish traders) in handling and managing the pindang fish they sell. Pindang fish contamination causes a decrease in the quality of pindang fish. Hygiene and sanitation factors from pindang fish traders are the background of this problem. The purpose of this study was to determine the relationship between hygiene and sanitation ofpindang fish traders with the number of bacteria in pindang fish in the Anom market, Kolor village, Sumenep district as a source of learning biology. This research was carried out in two stages. The first stage is filling out the observation sheet about sanitation hygiene requirements and the second stage is testing the number of bacteria in pindang fish using the Total Plate Count method. The results of this study indicate that there is a relationship between the hygiene and sanitation of pindang fish traders with the number of bacteria in pindang fish in the Anom market, Kolor village, Sumenep district as a source of learning biology. The results of the calculation on the coefficient of determination of 65.61%, this can be interpreted that as much as 65.61% of the number of bacteria in pindang fish is influenced by the sanitary hygiene of pindang fish traders, while as much as 34.39% is influenced by other factors, such as the environmental conditions of the market where traders selling pindang fish that are not clean and dirty so that it allows pindang fish to be polluted, the presence of disease-carrying insects around the pendang fish being sold. The conclusion of this study is that there is a relationship between the hygiene and sanitation of pindang fish traders with the number of pindang fish bacteria in the Anom market, Sumenep district as a source of learning biology